2010
DOI: 10.1016/j.powtec.2010.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of solid flow rate from pressure measurement in circulating fluidized bed

Abstract: A method is described to estimate solid mass flow rate based on measurement of pressure drop in horizontal section of circulating fluid bed (CFB). A theoretical model was derived based on momentum balance equation and used to predict the solids flow rate. Several approaches for formulating such models are compared and contrasted. A correlation was developed that predicts the solids flow rate as a function of pressure drop measured in the horizontal section of piping leading from the top of the riser to the cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…When gas and solids exit the vertical riser, the particles accelerate along the horizontal pipe along with the gas. The solids concentration is usually very low in the crossover [24], [25], [26], [27]. With a dilute flow of solids existing in the crossover, it is assumed that the average particle velocity (u p,co ) attains the value of the superficial gas velocity (U g,co ) suggesting a zero slip between the gas and solids (Eq.…”
Section: Solids Residence Time In the Risermentioning
confidence: 99%
“…When gas and solids exit the vertical riser, the particles accelerate along the horizontal pipe along with the gas. The solids concentration is usually very low in the crossover [24], [25], [26], [27]. With a dilute flow of solids existing in the crossover, it is assumed that the average particle velocity (u p,co ) attains the value of the superficial gas velocity (U g,co ) suggesting a zero slip between the gas and solids (Eq.…”
Section: Solids Residence Time In the Risermentioning
confidence: 99%
“…In Yang's experiment [29], the pressure drop between the riser exit and the inlet of the cyclone was fitted to the solid circulation rate, and a different formula from Patience was obtained. Monazam et al [30] tried to use a dimensionless quantity for revising the formula. The authors showed a more detailed consideration of parameters in same momentum balance equation and proposed a formula associating dimensionless solid flux G s ρ g v gh with the Euler number Eu: G s…”
Section: Correlations Based On Pressure Drop Of Other Placesmentioning
confidence: 99%
“…[ 11 ] To determine the solids circulation rate in both laboratory and commercial CFB systems, a number of devices, [ 12–15 ] techniques, [ 16–21 ] and methods [ 22–24 ] have been proposed and evaluated. The simplest method to estimate solids circulation rate is based on the measurement of pressure drops across different sections of the system, including the horizontal section between the exit of riser and the cyclone, [ 22,25 ] over the abrupt riser exit, [ 11 ] over the standpipe dense bed, [ 23 ] over the top section of the riser, [ 26 ] and over the whole riser. [ 27 ] To our knowledge, there has been no report on exploring the use of pressure drop between the riser inlet and the annulus in the bottom solids entrance region to determine G s in an a‐CFB system.…”
Section: Introductionmentioning
confidence: 99%